1992
DOI: 10.1111/j.1570-7458.1992.tb01568.x
|View full text |Cite
|
Sign up to set email alerts
|

Size specific demography of three species of Anastrepha fruit flies

Abstract: Individuals of three Anastrepha species: A. obliqua, A. ludens, and A. serpentina (Diptera: Tephritidae), were sorted according to pupal weight in cohorts of large and small flies. Demographic parameters and reproductive patterns and heterogeneity were determined for each cohort. Large flies of the three species presented greater expectation of life and gross fecundity rates. A. ludens was the species with the longest life span (expectation of life of large adults was 110 days) and the greatest gross fecundity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
47
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 17 publications
4
47
0
5
Order By: Relevance
“…The first had a longer oviposition period, greater egg production and shorter mean pre-oviposition period. These results for A. obliqua are similar to those reported by Liedo et al (1992) in a comparative study of this species with A. ludens and A serpentina. The latter had greater longevity as did A. sororcula and A. zenildae in the present study, and lower egg production.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The first had a longer oviposition period, greater egg production and shorter mean pre-oviposition period. These results for A. obliqua are similar to those reported by Liedo et al (1992) in a comparative study of this species with A. ludens and A serpentina. The latter had greater longevity as did A. sororcula and A. zenildae in the present study, and lower egg production.…”
Section: Discussionsupporting
confidence: 81%
“…Within this context similar survival strategies can be suggested between A. obliqua and A. fraterculus and between A. sororcula and A. zenildae. According to data from Liedo et al (1992), corroborated by this study, A. obliqua can be characterized as a species with high capacity to colonize because it presents a short life cycle and a very intense reproduction period.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Daily egg production for WS in this study was nine eggs per female, whereas Liedo et al (1992) and Liedo and Carey (1996) reported 17 and 14.9 eggs per female per d, respectively. This parameter represents the second signiÞcant change induced by colonization; the daily egg production increased to over 22 eggs per female in G 2 , with a maximum of 68, showing that A. obliqua adapted under laboratory conditions (OchiengOdero 1994).…”
Section: Discussionmentioning
confidence: 51%
“…Over the past two decades, demographic studies have deÞned the effect of the artiÞcial larval diet on mass-reared insects (Celedonio-Hurtado et al 1988) as well as the relationship between pupal size and life expectancy (Liedo et al 1992, Liedo andCarey 1994). In all these studies, wild ßies were compared with laboratory ßies from a single generation.…”
mentioning
confidence: 99%